DIAGNOSTIC ACCURACY OF CONTRAST-ENHANCED ULTRASOUND TO DIFFERENTIATE BENIGN AND MALIGNANT BREAST LESIONS - Ashar Pambudi, Radian (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Cancer of the breast is caused by a cluster of abnormal breast cells that continue to divide and spread throughout the breast. These cells eventually aggregate as a lump in the affected breast. If the cancerous tumor is not treated, the cancer cells may spread to other areas of the body through a process known as metastasis. A metastasis may develop in the lymph nodes located in the axilla or those located above the scapula. In addition, cancer cells have the ability to colonize the bones, lungs, liver, skin, and even the space directly under the skin. Cancer of the breast tissue is a malignancy that can start from either the ductal or lobule epithelium of the breast. Breast cancer is the most common kind of cancer in women. The ability of ultrasonography to identify cystic masses is one of the technology's many strengths. According to BIRADS, the American College of Radiology has also developed a standardized language for the reading and reporting of ultrasounds, which is quite similar to the language used for mammography. Shape of the mass, borders, orientation, kind of posterior acoustic, lesion boundaries, and echo pattern were the characteristics that were described. CEUS is an imaging technology that evaluates breast lesions by analyzing their qualitative qualities as well as their quantitative aspects. The detection of lymphatic channels and sentinel lymph nodes can be done using this method, and it is practical and effective.